\(Q=x^2-y^2-2y-1\)
\(\Rightarrow Q=x^2-\left(y^2+2y+1\right)\)
\(\Rightarrow Q=x^2-\left(y+1\right)^2\)
\(\Rightarrow Q=\left(x-y-1\right)\left(x+y+1\right)\)
Thay \(x=93;y=6\)vào \(Q\)ta được :
\(Q=\left(93-6-1\right)\left(93+6+1\right)\)
\(\Rightarrow Q=86.100\)
\(\Rightarrow Q=8600\)
Vậy \(Q=8600\)
P/s : Theo mình thì đây là cách nhanh nhất >:
~
\(Q=x^2-y^2-2y-1\)
\(Q=x^2-\left(y^2-2y+1\right)\)
\(Q=x^2-\left(y+1\right)^2\)
Thế x; y vào ya có:
\(Q=93^2-\left(6+1\right)^2\)
\(Q=8649-49\)
\(Q=8600\)
Vậy Q = 8600